Bio-kerosene and Bio-gasoil from Coconut Oils via Hydrocracking Process over Ni-Fe/HZSM-5 Catalyst - Muhammad Al-Muttaqii; Firman Kurniawansyah; Danawati Hari Prajitno; Achmad Roesyadi (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
In this study, hydrocracking of coconut oil over Ni-Fe/HZSM-5 catalyst was carried out in a batch reactor under different reaction temperature. Coconut oil is proposed as one of the potential feedstock for biofuel production. The Ni-Fe/HZSM-5 catalyst was prepared by incipient wetness impregnation method. The characterization of Ni-Fe/HZSM-5 catalyst by X-Ray Diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDAX), and Brunauer-Emmett-Teller (BET). The chemical composition of biofuel was analyzed by Gas-Chromatography-Mass Spectrometry (GC-MS). The results from the GC-MS analysis showed that the hydrocracking reaction over 10 % (Ni-Fe)/HZSM-5 catalyst at temperature of 375 oC obtained the highest hydrocarbon content (contained 49.4% n-paraffin, 26.93 % isoparaffin, 3.58 % olefin) and the highest yield of bio-gasoil 38.6 % in the biofuel liquid hydrocarbon. Pentadecane (n-C15) and heptadecane (n-C17) were the most abundant hydrocarbon compounds in biofuel liquid hydrocarbon. Decarboxylation and/or decarbonylation was the dominant reaction pathways in this process. Based on the result, the reaction temperature had a significant effect on the distribution of biofuel composition and yield of biofuel from coconut oil.